Election Administration in Nigeria: A Critique of the 2019 General Elections - UGWUIBE, Onyemaechi C.; UGWUANYI, Chigozie F.; UDENZE , Chukwudike; IHEJIRIKA, Ngozi O. (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2021)
Prior to the 2019 general elections in Nigeria, the Independent National Electoral Commission (INEC) had conducted five quadrennial general elections from 1999-2015. The 2019 elections were characterised by various anomalies which include but not limited to widespread rigging through multiple registrations, alteration of results at collation centres, etc. Hence, this study examines election administration in Nigeria with particular emphasis on 2019 general elections. Data for the study were basically selected from both primary and secondary sources. The study identified that poor operational logistics, weak institutional framework on the side of INEC among others, still remain a major challenge in the administration of the 2019 general elections. The paper recommends among others that adequate digitalisation of the electoral process is a necessity to prevent the possibility of street thugs destroying ballot boxes and votes, and forestalling postponement of subsequent elections in the future.